Analisis Komparasi Kesejahteraan Penduduk Provinsi: Studi Kasus Jawa Barat, Jawa Tengah dan Jawa Timur - Rustandi, Andi; Lestari Komarlina, Dwi Hastuti (Jurusan Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Siliwangi, 2021)
The imbalance of economic welfare between provinces can be analyzed, among other things, from the variation lag gap between income per capita and inflation. The research was carried out by observing the inequality in the provinces of West Java, Central Java and East Java, with the aim of knowing: the variations in per capita income of the population; variation in inflation; the comparison of the variation gap in inflation and per capita income of the population in those areas. The study used a descriptive analysis method by analyzing the coefficient of variation in per capita income and inflation as parameters. Comparison of the gap between the coefficient of variation in inflation and per capita income is analyzed to observe the existing welfare of the people of the three provinces. The results obtained from the study: (a) The average variation / fluctuation of income per capita of the population of West Java is more varied (fluctuating) than the average compared to the average variation in per capita income of the population of East Java and Central Java: (b) Variation / fluctuation of inflation in East Java is smaller so that it is considered that the average development rate of the expensive level in East Java is relatively lower than that of Central Java and West Java; (c) The average lag gap of inflation and the average per capita income of the population is actually higher than the percentage of per capita income, so that the welfare of the population in West Java, Central Java and East Java is considered to be less empowered and not prosperous.Ketimpangan kesejahteraan penduduk antarprovinsi dapat di antaranya dapat dianalisis dari lag gap variasi antara pendapatan perkapita dengan inflasi. Penelitian dilakukan dengan pengamatan ketimpangannya pada Provinsi Jawa Barat, Jawa Tengah dan Jawa Timur, dengan tujuan untuk mengetahui: variasi pendapatan per kapita Penduduk; Variasi inflasi; dan untuk menganalisis komparasi gap variasi inflasi dan pendapatan perkapita penduduk di Provinsi Jawa Barat, Jawa Tengah dan Jawa Timur. Penelitian menggunakan metoda analisis deskriptif dengan menganalisis parameter koefisien variasi pendapatan perkapita serta inflasi. Komparasi gap antara parameter koefisien variasi inflasi dengan pendapatan perkapita, digunakan untuk mengamati eksisting kesejahteraan masyarakat ketiga provinsi tersebut. Dari penelitian diperoleh hasil: (a) Rata-rata variasi/fluktuasi pendapatan perkapita penduduk Jawa Barat lebih bervariasi (fluktuatif) dari rata-ratanya dibandingkan rata-rata variasi pendapatan perkapita penduduk Jawa Timur dan Jawa Tengah: (b) Variasi/fluktuasiÂ inflasi di Jawa Timur lebih kecil sehingga dianggap rata-rata perkembangan tingkat kemahalan di Jawa Timur relatif lebih rendah dibanding dibanding Jawa Tengah dan Jawa Barat; (c) Lag gap rerata inflasi dan rerata pendapatan perkapita penduduk ternyata persentase inflasinya lebih tinggi dibanding persentase pendapatan perkapita, sehingga dimaknai kesejahteraan penduduk di Provinsi Jawa Barat, Jawa Tengah dan Jawa Timur dianggap kurang berdaya dan tidak sejahtera.